Analisis Penerapan Manajemen Risiko Kredit pada Perusahaan Start-Up Fintech PT A - Risyad Aditya Saputra; Nureni Wijayati (Politeknik Ganesha Medan, 2023)
Fintech PT A is one of the pioneers in Indonesia that serves business people with lenders on a digital platform. One of the problems faced by fintech PT A is the increase in non-performing loans. This research is a case study at a fintech startup to analyze the application of credit risk management and provide recommendations for improving credit risk management to improve company performance. The methodology used in this research is descriptive qualitative analysis by collecting data from interviews and documentation studies. Interviews were conducted with the Director of Credit and Collection and Director of Risk who have a crucial role in risk management in the company. The results of the study show that the application of risk management to PT A is in accordance with the four stages of the Indonesia’s Financial Services Authority regulation number 04/POJK.05/2021 namely credit risk identification, credit risk measurement, credit risk control, and credit risk monitoring. However, the application of credit risk management by PT A based on data analysis obtained through interviews and documentation studies shows that the results have not operate optimally. Because at the stages of monitoring credit risk and controlling credit risk there are still several aspects that have not been fulfilled based on the Indonesia’s Financial Services Authority regulation number 04/POJK.05/2021. So the recommendation that can be given is that the company can create a more structured and sustainable risk management system with all related divisions so that it can accommodate all aspects of risk up to the risk monitoring and control process.